Endowments, Location or Luck? Evaluating the Determinants of Sub-National Growth in Decentralized Indonesia - McCulloch, Neil; Sjahrir, Bambang Suharnoko (World Bank, Washington, DC, 2012)
Indonesia's "big bang" decentralization in 2001 shifted much of the responsibility for local economic development from central government to district and city governments, which today number more than 450. But the performance of these districts has varied widely. This paper attempts to understand the determinants of sub-national (district/city) growth in Indonesia and map how these determinants have changed since before the 1997/98 economic crisis. The authors exploit a rich dataset that includes a wide range of district-level characteristics, including education, population, cultural, economic, and infrastructure variables, as well as a set of variables relating to distance, to try to explain growth. The analysis finds that, after accounting for differences in other variables, poorer districts tend to grow faster than better off districts. Similarly, there is evidence of spatial divergence, in the sense that districts tend to grow faster if their neighbors are growing quickly. However, the quality of the existing district-level data makes it difficult to identify whether endowments or factors related to distance are systematically associated with growth.